2016
DOI: 10.19030/ajee.v7i2.9831
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control And Academic Performance In Engineering

Abstract: Self-control has been related to positive student outcomes including academic performance of college students.  Because of the critical nature of the first semester academic performance for engineering students in terms of retention and persistence in pursuing an engineering degree, this study investigated the relationship between freshmen engineering students’ scores on the Brief Self-Control Scale and first semester GPA. To identify the unique explanatory contribution of self-control beyond incoming academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
2
18
0
2
Order By: Relevance
“…Self-control has been linked to better academic performance as measured by grades (Feldmann & Martinez-Pons, 1995) and better psychological adjustment and interpersonal skills (Tangney et al, 2004) as well as better regulation of eating and alcohol consumption (Baumeister, 1994;Heatherton, 1993;Heatherton & Baumeister, 1991). Recent work has shown that self-control is predictive of first-year engineering students' GPA, explaining an additional 5% variance above that of ACT scores (Honken et al, 2016).…”
Section: Self-controlmentioning
confidence: 99%
“…Self-control has been linked to better academic performance as measured by grades (Feldmann & Martinez-Pons, 1995) and better psychological adjustment and interpersonal skills (Tangney et al, 2004) as well as better regulation of eating and alcohol consumption (Baumeister, 1994;Heatherton, 1993;Heatherton & Baumeister, 1991). Recent work has shown that self-control is predictive of first-year engineering students' GPA, explaining an additional 5% variance above that of ACT scores (Honken et al, 2016).…”
Section: Self-controlmentioning
confidence: 99%
“…Self‐report questionnaires are used to measure students’ future goals, self‐control and affect to school, which may be subject to response biases (Mega, Ronconi, & De Beni, ). In future studies, behavioral measures may be employed as well, such as the ability to stay on task and avoid digital distractions (Honken, Ralston, & Tretter, ). Last but not least, given the importance of self‐control for long‐term school success, it would be meaningful for future research to investigate and collect evidence on the interventions that are effective in promoting students’ self‐control in academic settings.…”
Section: Discussionmentioning
confidence: 99%
“…El autocontrol fue un predictor significativo del logro académico subjetivo (r=.33, p<.001). Más recientemente, Honken, et al, (2016) desarrollaron una investigación con el objetivo de investigar la relación entre las calificaciones de los estudiantes de primer año de Ingeniería con el autocontrol, con la finalidad de identificar la contribución de esta variable en el desarrollo académico de los jóvenes. Participaron estudiantes de tres cohortes (2012, 2013 y 2014) de primer año de Ingeniería (n= 1295).…”
Section: Diseños Empleados En El Estudio Del Autocontrol Y Rendimientunclassified
“…En la mayoria de los estudios analizados se encontraron altos niveles de correlación cuando el rendimiento académico se obtuvo por medio del reporte de las autoridades (calificaciones finales o promedios) o medidas objetivas (escalas de medición del desempeño académico) (Stadler et. al., 2016a;Zetler, 2011;Victoroff y Boyatzis, 2013;Kennett y Reed, 2009;Honken, et al, 2016). Cuando el autocontrol fue correlacionado con el rendimiento académico autodeclarado (calificación reportada por el estudiante) se encontraron resultados heterogéneos, en un caso presentó alta correlación (Alotaibi, 2016) y en otros casos se presentaron bajas correlaciones (King y Gaerlan, 2014;Knouse et al, 2014;Baars et al, 2015).…”
Section: Relaciones Entre Autocontrol Y Rendimiento Académicounclassified